2009
DOI: 10.1126/science.1172702
|View full text |Cite
|
Sign up to set email alerts
|

CD4 + Regulatory T Cells Control T H 17 Responses in a Stat3-Dependent Manner

Abstract: Distinct classes of protective immunity are guided by activation of STAT transcription factor (TF) family members in response to environmental cues. CD4+ regulatory T cells (Tregs) suppress excessive immune responses, and their deficiency results in a lethal, multi-organ autoimmune syndrome characterized by T helper 1 (Th1) and T helper 2 (Th2) CD4+ T cell-dominated lesions. Here we show that pathogenic Th17 responses in mice are also restrained by Tregs. This suppression was lost upon Treg-specific ablation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
730
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 888 publications
(760 citation statements)
references
References 28 publications
27
730
3
Order By: Relevance
“…However, it is not clear whether such Treg cells have intrinsically different suppressive function or whether they share common suppressive properties and the specificity is exerted mainly through local environmental adaptation. The latter hypothesis is supported by the observations that Treg cells isolated from these studies largely show intact suppressive activity in vitro (9)(10)(11)(12). We sought to approach this question by addressing whether transcriptionally diverse Treg cell subsets exist in humans, and whether the diversity accounts for potential differences in their in vitro functionality.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, it is not clear whether such Treg cells have intrinsically different suppressive function or whether they share common suppressive properties and the specificity is exerted mainly through local environmental adaptation. The latter hypothesis is supported by the observations that Treg cells isolated from these studies largely show intact suppressive activity in vitro (9)(10)(11)(12). We sought to approach this question by addressing whether transcriptionally diverse Treg cell subsets exist in humans, and whether the diversity accounts for potential differences in their in vitro functionality.…”
Section: Discussionmentioning
confidence: 92%
“…Several key studies have revealed a biased breakdown of tolerance when Treg cells are genetically mutated for particular genes. Specifically, Tregspecific deletion of T-bet, IFN regulatory factor 4, Stat3, and Bcl6 resulted in the impairment of specific regulation of Th1, Th2, Th17, and T follicular helper cells, respectively (9)(10)(11)(12). The finding that the key transcription factors for Th cell differentiation are also required for Treg cells to suppress these Teff cells suggests that the Treg population comprises multiple functional subsets, some of which may have a designated Th cell target.…”
Section: R Egulatory T (Treg) Cells Play a Key Role In Maintainingmentioning
confidence: 95%
“…However, all animals have naturally occurring Treg (nTreg) cells that confer basal suppression of effector cell functions; the depletion of nTreg cells results in the induction of autoimmune and/or inflammatory diseases, which are associated with enhanced autoreactive cellular immune responses (61). Therefore, it is common that total Treg cell depletion in mice results in stronger cellular immune responses than do those in Treg cell-competent mice, and this could be observed with any kind of infection (62,63). A strategy to deplete virus-induced Treg cells alone, without affecting the numbers and functions of nTreg cells, would be necessary to precisely determine the role of induced Treg cells in vivo, which has never been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In addition, Treg-specific deletion of the transcription factors IRF4 (interferon regulatory factor 4) or STAT3 (signal transducer and activator of transcription 3) resulted in an impaired regulation of Th2-and Th17-dominated immune responses, respectively. 15,16 Recently, a population of germinal center-resident Tregs, termed follicular regulatory T cells, was identified. 17,18 These follicular regulatory T cells suppress germinal center B and T cells and depend, similar to their follicular T helper cell counterparts, on the expression of the transcription factor Bcl6 for their development.…”
Section: Introductionmentioning
confidence: 99%